Transcriptome characterization of moso bamboo (Phyllostachys edulis) seedlings in response to exogenous gibberellin applications - Zhang, Hangxiao; Wang, Huihui; Zhu, Qiang; Gao, Yubang; Wang, Huiyuan; Zhao, Liangzhen; Wang, Yongsheng; Xi, Feihu; Wang, Wenfei; Yang, Yanqiu; Lin, Chentao; Gu, Lianfeng (BMC plant biology, 2018)
Moso bamboo (Phyllostachys edulis) is a well-known bamboo species of high economic value in the textile industry due to its rapid growth. Phytohormones, which are master regulators of growth and development, serve as important endogenous signals. However, the mechanisms through which phytohormones regulate growth in moso bamboo remain unknown to date. Here, we reported that exogenous gibberellins (GA) applications resulted in a significantly increased internode length and lignin condensation. Transcriptome sequencing revealed that photosynthesis-related genes were enriched in the GA-repressed gene class, which was consistent with the decrease in leaf chlorophyll concentrations and the lower rate of photosynthesis following GA treatment. Exogenous GA applications on seedlings are relatively easy to perform, thus we used 4-week-old whole seedlings of bamboo for GA- treatment followed by high throughput sequencing. In this study, we identified 932 cis-nature antisense transcripts (cis-NATs), and 22,196 alternative splicing (AS) events in total. Among them, 42 cis-nature antisense transcripts (cis-NATs) and 442 AS events were differentially expressed upon exposure to exogenous GA , suggesting that post-transcriptional regulation might be also involved in the GA response. Targets of differential expression of cis-NATs included genes involved in hormone receptor, photosynthesis and cell wall biogenesis. For example, LAC4 and its corresponding cis-NATs were GA -induced, and may be involved in the accumulation of lignin, thus affecting cell wall composition. This study provides novel insights illustrating how GA alters post-transcriptional regulation and will shed light on the underlying mechanism of growth modulated by GA in moso bamboo.